Evaluation of Chemical Constituents and Antioxidant Activity of Extracts of Nardostachys jatamansi (D. Don) DC. - Budha, Rajkumar; Maharjan, Binita; Panta, Ritu; Bharati, Samjhana; Shrestha, Timila; Homagai, Puspa Lal; Bhattarai, Deval Prasad; Shrestha, Ram Lal Swagat (Amrit Research Journal, 2023)
Nardostachys jatamansi is an endangered medicinal plant of the Caprifoliaceae family. The main aim of this study was to evaluate the metabolites and their biological activities. The shade dried, powdered plant materials were subjected to successive ultrasonic extraction with solvents hexane, chloroform, ethyl acetate, and methanol in the increasing order of polarity. Flavonoids, terpenoids, saponins, phenolic volatile oils, and alkaloids were discovered in the phytochemical screening. Gas chromatography mass spectrometry analysis identified 13, 10, and 6 chemical compounds in hexane, chloroform, and ethyl acetate extracts, respectively. Cyclic saturated hydrocarbons, organic acids, alcohol, and ester were the main constituents of extracts verified by GC-MS. Chloroform extracts had a higher phenolic content (49.53 mg GAE/g) than ethyl acetate extracts (44.41 mg GAE/g).  Chloroform extracts had a higher total flavonoid concentration (18.42 mg QE/g) than ethyl acetate extracts (10.57 mg QE/g).  The half-maximum inhibitory concentration (IC50) of the chloroform and ethyl acetate extracts revealed moderate results to antioxidant activity.